Akulturasi Islam dan Budaya Jawa dalam Tradisi Kupatan 15 Ruwah dan 7 Syawal Masyarakat Tuban - Mustafa Ali Maskur; Atalafairus Iklil Warsanda; Nurul Hakim (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the dynamics of acculturation between Islamic doctrines and Javanese culture within the Kupatan 15 Ruwah and 7 Syawal traditions in the Tuban community. The Kupatan tradition is explored as a socio-religious practice rich in symbolic and spiritual significance that remains preserved today. Employing a qualitative case study design, data were gathered through field observations, in-depth interviews, and documentation. The findings reveal that the Kupatan 15 Ruwah and 7 Syawal traditions represent a harmonious synthesis of normative Islamic values and local Javanese wisdom. Kupatan 15 Ruwah is oriented toward prayer and spiritual preparation for Ramadan, aligning with the Islamic concept of self-reflection (muhasabah). Conversely, Kupatan 7 Syawal actualizes gratitude, social cohesion (silaturahmi), and community philanthropy through post-fasting sharing rituals. Semiotically, the morphology of the ketupat constructs profound philosophical meanings, such as acknowledging faults (ngaku lepat) and seeking spiritual purification, which closely resonate with Islamic tenets. Furthermore, this rite functions as an effective and persuasive strategy for cultural da'wah. However, the currents of modernization pose unique sociological challenges, particularly the risk of value degradation and declining participation among the younger generation. This study concludes that the Kupatan tradition in Tuban is not merely a ceremonial heritage but a vital integration of religion and culture that demands preservation. This research is expected to contribute to local wisdom-based Islamic studies and reinforce collective awareness in safeguarding religiously grounded traditions.   Keywords: Acculturation, Islam, Javanese culture, Kupatan tradition, Tuban